Hemispheric speech lateralisation in the developing brain is related to motor praxis ability - Jessica C. Hodgson; Rebecca J. Hirst; John M. Hudson (Developmental Cognitive Neuroscience, 2016)
Commonly displayed functional asymmetries such as hand dominance and hemispheric speech lateralisation are well researched in adults. However there is debate about when such functions become lateralised in the typically developing brain. This study examined whether patterns of speech laterality and hand dominance were related and whether they varied with age in typically developing children. 148 children aged 3–10 years performed an electronic pegboard task to determine hand dominance; a subset of 38 of these children also underwent functional Transcranial Doppler (fTCD) imaging to derive a lateralisation index (LI) for hemispheric activation during speech production using an animation description paradigm. There was no main effect of age in the speech laterality scores, however, younger children showed a greater difference in performance between their hands on the motor task. Furthermore, this between-hand performance difference significantly interacted with direction of speech laterality, with a smaller between-hand difference relating to increased left hemisphere activation. This data shows that both handedness and speech lateralisation appear relatively determined by age 3, but that atypical cerebral lateralisation is linked to greater performance differences in hand skill, irrespective of age. Results are discussed in terms of the common neural systems underpinning handedness and speech lateralisation. Keywords: Speech production, Lateralization, Transcranial Doppler, Motor control, Development